2022
DOI: 10.3390/app12146992
|View full text |Cite
|
Sign up to set email alerts
|

Load Transfer Behavior and Failure Mechanism of Bird’s Nest Anchor Cable Anchoring Structure

Abstract: To research the internal load transfer behavior and failure mechanism of a bird’s nest anchor cable anchoring structure based on a pull-out test, a bond-slip failure model is established on the basis of statistical damage theory, and the distribution formula of shear stress at anchorage agent–rock interface is deduced. Combined with theoretical analysis, bird’s nest anchor cable pulling out test and particle flow code (PFC) numerical simulation test, as well as axial force distribution of the cable and shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Alonso et al [16] assessed the development of intelligent transportation systems and other technologies regarding the promotion of population mobility by investigating 1414 Dominicans aged between 18 and 40, and proposed the need to strengthen the information and communication flow of emerging transportation-related technologies. Zhu et al [17] revealed the internal load transfer behavior and failure mechanism of the bird's nest anchor cable anchored structure through theoretical analysis, bird's nest anchor cable pull-out test, and particle flow program numerical simulation test. The authors proposed that the failure mode was the combination of the interface debonding and sliding and rock shear failure.…”
mentioning
confidence: 99%
“…Alonso et al [16] assessed the development of intelligent transportation systems and other technologies regarding the promotion of population mobility by investigating 1414 Dominicans aged between 18 and 40, and proposed the need to strengthen the information and communication flow of emerging transportation-related technologies. Zhu et al [17] revealed the internal load transfer behavior and failure mechanism of the bird's nest anchor cable anchored structure through theoretical analysis, bird's nest anchor cable pull-out test, and particle flow program numerical simulation test. The authors proposed that the failure mode was the combination of the interface debonding and sliding and rock shear failure.…”
mentioning
confidence: 99%